Eating disorders, body image and media exposure among adolescent girls in rural Burkina Faso - Terhoeven, Valentin; Nikendei, Christoph; Bärnighausen, Till; Bountogo, Mamadou; Friederich, Hans-Christoph; Ouermi, Lucienne; Sié, Ali; Harling, Guy (Tropical medicine & international health, 2020)
Objective - Body dissatisfaction and eating disorders (ED) among young females may increase in limited-resource settings as exposure to media and higher-resource cultures increases. We examined ED prevalence and its predictors among adolescent girls in rural north-western Burkina Faso.
First published: 11 November 2019
Gesehen am 12.01.2022